Regulation's influence on EU banking efficiency: An evaluation post crisis - Edward Bace; Ana Ferreira (Cogent Economics & Finance, 2020)
This paper examines the impact of regulatory policies on banking market efficiency using a sample of 678 commercial banks from 21 European Union countries for the post-crisis year 2010, controlling for bank-specific and country-specific variables. Data on regulation, supervision and monitoring variables, and activity restrictions are from the most recent Bank Regulation and Supervision Survey database conducted by the World Bank, published 2012. Besides these we incorporate bank size, equity, market share, government ownership, and growth of Gross Domestic Product per capita, employing an Ordinary Least Squares method. Focus is on two alternative measures of banking market efficiency: net interest margin and overhead costs (operating expenses to assets). Elevated levels of these two ratios should indicate a low level of banking efficiency. The evidence suggests that the link between capital regulation and banking efficiency is not robust enough to control for other regulatory variables. Results confirm that activity restrictions have a negative and significant impact on banking efficiency. Policies encouraging official supervisory power do not enhance efficiency of the banking sector. The only approach positively and statistically significantly associated with efficiency is private monitoring. This leads to the suggestion that government regulation and supervision should be more focused on promoting transparency of information.
Keywords: G14; G21; G28; 330; banking; efficiency; European Union; regulation